Determination of Patient Satisfaction with Dental and Oral Care Services for Clinical Students at Dental and Oral Hospital Prima Medan - Silvi Tiara Dewi; Chrismis Novalinda Ginting; Maya Sari Mutia (Postgraduate, University of Mataram, 2023)
The aim of this research is to determine the determinants of patient satisfaction with dental and oral care services for clinical students at Dental and Oral Hospital Prima Medan. This type of research is quantitative research with a cross-sectional design. The sample in this study was 200 patients. Data analysis in this study used univariate, bivariate and multivariate analysis. The results of the study showed that there was a correlation between patient satisfaction with dental and oral care services among clinical students at Dental and Oral Hospital Prima Medan based on time, procedure, attitude, level of knowledge, p < 0.05 (0.000 < 0.05) with a very high correlation level strong. There is a correlation between patient satisfaction with dental and oral care services among clinical students at Dental and Oral Hospital Prima Medan based on communication and spatial comfort, p < 0.05 (0.000 < 0.05) with a strong correlation level. The influence of service time, procedures, attitudes, level of knowledge, communication and spatial comfort on dental and oral care patient satisfaction among clinical students at Dental and Oral Hospital Prima Medan was 83.7%. The variable that most influences patient satisfaction with dental and oral care services for clinical students at Dental and Oral Hospital Prima Medan is the procedure variable